(untitled) (Research, Society and Development, 2020)
Mango production in the Brazilian semiarid region has gained prominence in the national scenario due to the high yield and long production period using techniques that help in the main culture stages. The aim of this work was to evaluate the use of two alternative techniques in the production of ‘Palmer’ mango in the vegetative phase. It was evaluated whether commercial potassium-based Multipotássio® fertilizer could be used as an alternative source of potassium nutrient in the maturation process of mango branches, and whether Ascophyllum nodosum algae extract MultiTurbo® biostimulant would be good alternative for fruit production. Two experiments were conducted in the same area, the first experiment with factors represented by four Multipotássio® concentrations (0; 1; 2 and 3 L ha-1) and two assessment periods in the maturation of mango branches and leaves. In the second experiment, conducted in the same area, factors Multipotássio® concentration (0; 1; 2 and 3 L ha-1) and four MultiTurbo® concentrations (0; 0.625 ml ha-1; 1. 25 ml ha-1 and 2.50 ml ha-1) were evaluated. Number and length of panicles, carbohydrate content in branches and leaves, fruiting rate, fruit mass, length and diameter and yield were evaluated. The use of potassium-based fertilizer helps to increase sugar content in ’Palmer’ mango branches, which has been increasing in relation to the doses used. Biostimulants result in positive effects on the number of panicles, fruits and yield of ’Palmer’ mango.